(untitled) (UNIZIK Journal of STM Education, 2019)
The study focused on the effects of use of improvised consumable chemical substances in instructional delivery on secondary school students’ achievement in chemistry. Two research questions guided the study and three hypotheses were tested at 0.05 level of significance. The study adopted quasi-experimental design specifically, the pre-test post-test control group non-equivalent group design. The population of the study consisted of 12, 509 secondary school year one (SS1) students offering chemistry in Onitsha Education Zone of Anambra State. The sample size for the study was 101 chemistry SS1 students. The instrument used for data was Chemistry Achievement Test (CAT). The instrument was validated by lecturers in the Department of Science Education and Department of Educational Foundations, Nnamdi Azikiwe University Awka and one experienced chemistry teacher at Federal Science and Technical College, Awka. CAT reliability was established using Kuder Richardson 20 (KR20) which yielded reliability coefficient of 0.81. Data relating to the research questions was answered using mean and standard deviation and the hypotheses were tested using analysis of covariance (ANCOVA). The findings of the study revealed that the effects of the use of improvised consumable chemical substances on the achievement of chemistry students when compared to those taught using standard consumable chemical substances is not significantly different. The study recommended among others that chemistry teachers should use as an alternative to standard consumable chemical substances, improvised consumable chemical substances in the teaching and learning of practical chemistry.